This preview shows page 1. Sign up to view the full content.
51. We solve for
m
using the formula
r
=
p
(2
m
+1)
Rλ/
2 obtained in problem 49 and Fnd
m
=
r
2
/Rλ
−
1
/
2.
Now, when
m
is changed to
m
+ 20,
r
becomes
r
0
,so
m
+20=
r
0
2
/Rλ
−
1
/
2. Taking the di±erence
between the two equations above, we eliminate
This is the end of the preview. Sign up
to
access the rest of the document.
This note was uploaded on 11/12/2011 for the course PHYS 2001 taught by Professor Sprunger during the Fall '08 term at LSU.
 Fall '08
 SPRUNGER
 Physics

Click to edit the document details